Interferons in the Therapy of Severe Coronavirus Infections: A Critical Analysis and Recollection of a Forgotten Therapeutic Regimen with Interferon Beta - Brzoska, Josef; von Eick, Harald; Hündgen, Manfred (Drug Research, 2020)
The pharmacological and immunological properties of interferons, especially those of interferon beta, and the corresponding treatment strategies are described, and the results of studies with different interferons in coronavirus infections are analysed. Furthermore, the data obtained with high-dosed native interferon beta in life-threatening acute viral diseases as well as the results of clinical pilot studies with high-dosed recombinant interferon beta-1a are provided because they serve as the rationale for the proposed therapeutic regimen to be applied in acute viral infections. This regimen differs from those approved for treatment of multiple sclerosis and consists of interferon beta-1a administered as a 24 hour intravenous infusion at a daily dose of up to 90 µg for 3–5 consecutive days. Since under this regimen transient severe side effects can occur, it is analysed which patients are suitable for this kind of treatment in general and if patients with severe coronavirus infections could also be treated accordingly.
Keywords: antiviral drugs; cytokines; drug research; human pharmacology; infectious diseases; immunopharmacology; SARS; MERS; COVID-19; SARS-CoV-2